The prevalence, diagnostic accuracy and genotype-phenotype correlation of GNAS mutations in fibrous dysplasia: a meta-analysis - Zhang, Ao-Bo; Zhang, Jian-Yun; Xue, Jiang; Wu, Zhen-Chao; Xu, Zhi-Xiu; Sun, Li-Sha; Li, Tie-Jun (Frontiers in Genetics, 2024)
Background: There is inconsistent evidence regarding the accuracy of GNAS mutations identification for the diagnosis of FD/MAS. This study was performed to estimate the prevalence and diagnosis accuracy of GNAS mutations detection and preliminarily investigate the genotype-phenotype correlation in FD.Methods: Five electronic databases were searched from 1995 to 2024 using search terms related to GNAS and fibrous dysplasia. Observational studies of FD patients undergoing GNAS mutation detection in FD were included.Results: Total 878 FD patients were included. The pooled prevalence of GNAS mutations in FD based on the random effects model was 74% (95% CI= 64% to 83%). Regarding diagnostic accuracy, a sensitivity of 0.83 (95% CI, 0.65 to 0.96), specificity of 0.99 (95% CI, 0.98 to 1.00) and the area under the receiver operating characteristic curve of 98.38% were found. Additionally, meta-analysis and Fisher's test showed the GNAS mutation types were significantly associated with FD types (OR = 3.51, 95% CI = 1.05 to 11.72; p < 0.05).A high detection rate of GNAS mutation occurred in FD, and its detection is reliable for diagnosing FD. Additionally, GNAS mutation types were significantly associated with FD types.